The Possibilities of Assessing the Quality of Life in Inflammatory Bowel Diseases - Anna L. Arakelyan; Andrej N. Surkov; Evgenij E. Bessonov; Yuliya Yu. Popova; Anna A. Tsaturova; Denis A. Alekseev; Dar’ya V. Bychkova; Arina A. Gryaznova (Педиатрическая фармакология)
Inflammatory bowel diseases (IBD) in children are chronic immune-mediated conditions that significantly affect the quality of life (QOL). QOL assessment tools designed specifically for children allow us to quantify the degree of the disease’s impact on various aspects of their lives, such as daily activity, emotional state, social interactions, etc. The research results demonstrate that IBD has a negative impact on children’s QOL, leading to lower school performance, limited social activity, and psychological problems such as anxiety and depression. The severity of the disease, the frequency of exacerbations, the presence of symptoms, extra-intestinal manifestations, the need to follow a diet, frequent hospitalization, and side effects of drug therapy are factors associated with lower QOL. Improving QOL is one of the key goals of treatment, along with achieving clinical and endoscopic remission. Interventions aimed at improving QOL in children with IBD include pharmacological therapy, nutritional support, and psychosocial care. Regular QOL assessment allows doctors and parents to better understand the child’s needs, identify problem areas, and develop customized strategies aimed not only at controlling the disease, but also at improving overall well-being. The article summarizes data on existing methods for assessing QOL in pediatrics, including in the pathology of the gastrointestinal tract and, in particular, in IBD.